HUBUNGAN GASTROESOPHAGEAL REFLUX DISEASE DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - MUHAMMAD SALIM HAFIZH; DEBBY MIRANI LUBIS (JURNAL ILMIAH MAKSITEK, 2021)
Gastroesophageal reflux disease (GERD) is defined as a disorder in which stomach contents repeatedly rise into theesophagus causing a disturbance. Gastroesophageal reflux disease (GERD) is a common gastrointestinal disease aroundthe world that suffers from the quality of life problems, especially the quality of sleep. To determine the relationship betweenGastroesophageal reflux disease (GERD) and quality of sleep among medical students of Muhammadiyah Sumatera UtaraUniversity. This study used the descriptive analytic method with approach cross sectional. The samples are medical studentsof Muhammadiyah Sumatera Utara University class 2017, 2018, and 2019. The data analyzed using chi-square test.The result of the bivariate analysis of Gastroesophageal reflux disease (GERD) and quality of sleep shows the number of p =0,004 (p<0,05). There is significant relationship between Gastroesophageal reflux disease (GERD) and quality of sleepamong medical students of Muhammadiyah Sumatera Utara University.